Development and Validation of a Polygenic Risk Score for Stroke in the Chinese Population. (10th August 2021) - Lu, Xiangfeng; Niu, Xiaoge; Shen, Chong; Liu, Fangchao; Liu, Zhongying; Huang, Keyong; Wang, Laiyuan; Li, Jianxin; Hu, Dongsheng; Zhao, Yingxin; Yang, Xueli; Lu, Fanghong; et al.
Abstract : Objective: To construct a polygenic risk score (PRS) for stroke and evaluate its utility in risk stratification and primary prevention for stroke. Methods: Using a meta-analytic approach and large genome-wide association results for stroke and stroke-related traits in East Asians, we generated a combined PRS (metaPRS) by incorporating 534 genetic variants in a training set of 2, 872 patients with stroke and 2, 494 controls. We then validated its association with incident stroke using Cox regression models in large Chinese population-based prospective cohorts comprising 41, 006 individuals. Results: During a total of 367, 750 person-years (mean follow-up 9.0 years), 1, 227 participants developed stroke before age 80 years. Individuals with high polygenic risk had an about 2-fold higher risk of incident stroke compared with those with low polygenic risk (hazard ratio [HR] 1.99, 95% confidence interval [CI] 1.66–2.38), with the lifetime risk of stroke being 25.2% (95% CI 22.5%–27.7%) and 13.6% (95% CI 11.6%–15.5%), respectively. Individuals with both high polygenic risk and family history displayed lifetime risk as high as 41.1% (95% CI 31.4%–49.5%). Individuals with high polygenic risk achieved greater benefits in terms of absolute risk reductions from adherence to ideal fasting blood glucose and total cholesterol than those with low polygenic risk. Maintaining favorable cardiovascular health (CVH) profile could substantially mitigate the increased risk conferred by high polygenic risk to the level of low polygenic risk (from 34.6% to 13.2%). Conclusions: Our metaPRS has great potential for risk stratification of stroke and identification of individuals who may benefit more from maintaining ideal CVH. Classification of Evidence: This study provides Class I evidence that metaPRS is predictive of stroke risk.